Overview of New ESC Clinical Practice Guidelines for 2015. Issue 28 (29th October 2015) - Rizzo, Toni
The recently published 2015 European Society of Cardiology guidelines have been updated based on the wealth of new evidence from clinical trials in the different specialties. These timely and comprehensive guidelines offer guidance for clinicians on the latest management strategies for ventricular arrhythmias and sudden cardiac death, pulmonary hypertension, infective endocarditis, and acute coronary syndromes without ST-segment elevation.